2008
DOI: 10.1002/ffj.1850
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of Myrtaceae essential oils and their components against three phytopathogenic fungi

Abstract: Commercial plant essential oils obtained from 11 Myrtaceae plant species were tested for their antifungal activity against Phytophthora cactorum, Cryponectria parasitica and Fusarium circinatum. Good antifungal activity against Phytophthora cactorum was achieved with the essential oil derived from Leptospermum petersonii at 28 × 10 −3 mg/ml air concentration. Inhibition rates of Eucalyptus citriodora and Melaleuca quinquenervia were 35.4% and 33.6% at 28 × 10 −3 mg/ml air concentration, respectively. In a test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
1
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 17 publications
10
92
1
10
Order By: Relevance
“…The present study showed a dose-dependent relationship between the tested fungi and the essential oil concentrations as similarly reported in literature (Mishra et al, 2015;Silva et al, 2008). The GC-MS analysis showed the presence of linalool (0.21%), citronellal (45.09%) and citronellol (19.11%) as the main contributors toward the broad antifungal activities (Chand et al, 2016;Lee et al, 2008;Olorunnisola et al, 2014;Pauli and Knobloch, 1987).…”
Section: Antifungal Activities Of Selected Essential Oilssupporting
confidence: 87%
“…The present study showed a dose-dependent relationship between the tested fungi and the essential oil concentrations as similarly reported in literature (Mishra et al, 2015;Silva et al, 2008). The GC-MS analysis showed the presence of linalool (0.21%), citronellal (45.09%) and citronellol (19.11%) as the main contributors toward the broad antifungal activities (Chand et al, 2016;Lee et al, 2008;Olorunnisola et al, 2014;Pauli and Knobloch, 1987).…”
Section: Antifungal Activities Of Selected Essential Oilssupporting
confidence: 87%
“…The antifungal activities of α-pinene, β-pinene, myrcene, p-cymene, 1,8-cineole, limonene, γ-terpinene, linalool, terpinen-4-ol, α-terpineol, geraniol and β-caryophyllene against two phytopathogens tested in this study have been reported in an earlier study. 16 Two phenols (thymol and carvacrol) showed very strong antifungal activity against P. cactorum and C. parasitica at 28 × 10 -3 mg/ml air concentration, but there was a signi¼cant difference in antifungal activity at lower concentrations. The position of the hydroxyl group (-OH) is the only difference in the chemical structures of the two phenols.…”
Section: Discussionmentioning
confidence: 97%
“…Jointly or independently, they contribute to antifungal, insecticidal or nematicidal activities. [5][6]16 We analysed 17 and 20 volatile compounds from bay and red thyme oils, respectively, by GC-MS. Chemical components of red thyme and bay oils have been well studied. [7][8] Similar results were obtained in our analysis, although there was some difference in the ratios of chemicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the continued and indiscriminate use of pesticides causes a host of environmental and humanhealth problems, such as the interruption of natural biological control (SOYLU; KURT;SOYLU, 2010), resistance by pathogens causing outbreaks of disease (LEE et al, 2008) and contamination of ground and surface water (FERNANDES NETO;SARCINELLI, 2009). …”
Section: Introductionmentioning
confidence: 99%